2010
DOI: 10.1128/iai.01000-09
|View full text |Cite
|
Sign up to set email alerts
|

Waging War against UropathogenicEscherichia coli: Winning Back the Urinary Tract

Abstract: Urinary tract infection (UTI) caused by uropathogenic Escherichia coli (UPEC) is a substantial economic and societal burden-a formidable public health issue. Symptomatic UTI causes significant discomfort in infected patients, results in lost productivity, predisposes individuals to more serious infections, and usually necessitates antibiotic therapy. There is no licensed vaccine available for prevention of UTI in humans in the United States, likely due to the challenge of targeting a relatively heterogeneous g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
170
0
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(189 citation statements)
references
References 293 publications
(302 reference statements)
3
170
0
16
Order By: Relevance
“…In Europe, two vaccines against UTIs called SolcoUrovac and Uro-Vaxom are licensed for use in women with recurrent UTIs (16). SolcoUrovac is a vaginal suppository containing 10 heat-killed UPEC strains that provides relatively poor protection in the absence of frequent administration (17).…”
mentioning
confidence: 99%
“…In Europe, two vaccines against UTIs called SolcoUrovac and Uro-Vaxom are licensed for use in women with recurrent UTIs (16). SolcoUrovac is a vaginal suppository containing 10 heat-killed UPEC strains that provides relatively poor protection in the absence of frequent administration (17).…”
mentioning
confidence: 99%
“…It has been shown that bacterial pathogens deficient in type I or P pili are strongly attenuated in their ability to cause UTIs [65]. A major aim of studying the nanomachines involved in bacterial pathogenesis is to exploit the detailed structural knowledge to move from the current non-specific antibiotic treatments causing growing problems with resistance and therefore with chronic infections to more specific treatments targeting virulence factors.…”
Section: Resultsmentioning
confidence: 99%
“…It is part of the normal flora of the intestine of human and vertebrates. In spite of this, some strains of E. coli can cause gastroenteritis, urinary tract infection [31] as well as diarrhoea in infant [32]. Therefore, identification of this bacterium in the pito samples could merit public health attention.…”
Section: Discussionmentioning
confidence: 99%